The association between pain and sleep in fibromyalgia - Keskindag, Buse (Saudi Med J, 2017)
OBJECTIVE: To clarify the association between pain and sleep in fibromyalgia. METHODS: Electronic databases, including PsycINFO, the Cochrane database for systematic reviews, PubMed, EMBASE, and Ovid were searched to identify eligible articles. Databases independently screened and the quality of evidence using a reliable and valid quality assessment tool was assessed. RESULTS: In total, 16 quantitative studies fulfilled the inclusion criteria. According to the results, increased pain in fibromyalgia was associated with reduced sleep quality, efficiency, and duration and increased sleep disturbance and onset latency and total wake time. Remarkably, depressive symptoms were also related to both pain and sleep in patients with fibromyalgia. CONCLUSION: Management strategies should be developed to decrease pain while increasing sleep quality in patients with fibromyalgia. Future studies should also consider mood disorders and emotional dysfunction, as comorbid conditions could occur with both pain and sleep disorder in fibromyalgia.